Structural and Energetic Basis for Differential Binding of Ebola and Marburg Virus Glycoproteins to a Bat-Derived Niemann-Pick C1 Protein - Igarashi, Manabu; Hirokawa, Takatsugu; Takada, Ayato (The Journal of infectious diseases, 2023)
Abstract Background Our previous study demonstrated that the fruit bat (Yaeyama flying fox)-derived cell line FBKT1 showed preferential susceptibility to Ebola virus (EBOV), whereas the human cell line HEK293T was similarly susceptible to EBOV and Marburg virus (MARV). This was due to 3 amino acid differences of the endosomal receptor Niemann-Pick C1 (NPC1) between FBKT1 and HEK293T (ie, TET and SGA, respectively, at positions 425–427), as well as 2 amino acid differences at positions 87 and 142 of the viral glycoprotein (GP) between EBOV and MARV. Methods/Results To understand the contribution of these amino acid differences to interactions between NPC1 and GP, we performed molecular dynamics simulations and binding free energy calculations. The average binding free energies of human NPC1 (hNPC1) and its mutant having TET at positions 425–427 (hNPC1/TET) were similar for the interaction with EBOV GP. In contrast, hNPC1/TET had a weaker interaction with MARV GP than wild-type hNPC1. As expected, substitutions of amino acid residues at 87 or 142 in EBOV and MARV GPs converted the binding affinity to hNPC1/TET. Conclusions Our data provide structural and energetic insights for understanding potential differences in the GP-NPC1 interaction, which could influence the host tropism of EBOV and MARV. Consistent with the previously shown experimental findings, our computational study revealed that some amino acid differences in the filovirus receptor NPC1 among bat species could affect the binding affinity of ebolavirus and marburgvirus glycoproteins to the NPC1 molecule.